2017
DOI: 10.3892/etm.2017.4305
|View full text |Cite
|
Sign up to set email alerts
|

C-X-C motif chemokine ligand 8 promotes endothelial cell homing via the Akt-signal transducer and activator of transcription pathway to accelerate healing of ischemic and hypoxic skin ulcers

Abstract: Abstract. C-X-C motif chemokine ligand 8 (CXCL-8) promotes cell homing and angiogenesis. However, under hypoxic conditions, the role of CXCL-8 in the homing of human umbilical vein endothelial cells (HUVECs), and its effect on the healing of skin ulcers caused by ischemia and hypoxia remain unknown. In the current study, assays measuring cell proliferation, in vitro angiogenesis and cell migration were performed to evaluate alterations in the proliferation, angiogenic capacity and chemotaxis of HUVECs treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Calcium signals induce vascular endothelial cells or smooth muscle cells to contract microfilaments and microtubules, causing cell migration, sprouting, and growth of blood vessels, which effectively regulates blood vessel diameter and contributes to the remodeling of heart function [36] . Inflammatory factors such as IL-1 and IL-8 cause migration of vascular endothelial cells, angiogenesis, and typical inflammatory reactions [37] , [38] . VEGF is a very clear cytokine that promotes blood vessel growth.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium signals induce vascular endothelial cells or smooth muscle cells to contract microfilaments and microtubules, causing cell migration, sprouting, and growth of blood vessels, which effectively regulates blood vessel diameter and contributes to the remodeling of heart function [36] . Inflammatory factors such as IL-1 and IL-8 cause migration of vascular endothelial cells, angiogenesis, and typical inflammatory reactions [37] , [38] . VEGF is a very clear cytokine that promotes blood vessel growth.…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al found that CXCL-8 plays a critical regulatory function in angiogenic tissue repair by inducing vascular endothelial cells to secrete cytokines like VEGF and SOD when skin injury happens. 106 Through binding to CXCR2 on endothelial cells, CXCL-8 secreted by GBM cells promotes GBM angiogenesis and mesenchymal characteristics. 107 Moreover, up-regulation of Bcl-xL protein in GBM triggers the CXCL-8/CXCR2 axis, which leads to the stimulation of biological processes like cell proliferation, endothelial cell migration, and the formation of vital vascular structures in the central lumen.…”
Section: Paracrine Pathwaysmentioning
confidence: 99%